Language and the making of modern India : nationalism and the vernacular in colonial Odisha, 1803-1956 - Mishra, Pritipuspa (Cambridge University Press, 2020)
Introduction: Nation in the vernacular -- How the Vernacular Became Regional -- Vernacular Publics: A modern Odia readership imagined -- The Odia Political Subject and the Rise of the Odia Movement -- The Odia Political Subject and the Rise of the Odia Movement -- Odisha as Vernacula Homeland -- The Invisible Minority: History and the Problem of the Adivasi -- The Genius of India: Linguistic Difference, Regionalism and the Indian Nation.